Theoretical Basis of Reichenbach’s Philosophy - Nekrašas, Evaldas (Problemos, 1979)
The article deals with Reichenbach’s conception of sense, probability and induction which is fundamental in his philosophy. Other major questions discussed include: relation between Reichenbach’s probability theory of sense and his statistical interpretation of probability; pragmatic justification of induction; comparative analysis of the views of Reichenbach and Carnap on the above questions. In conclusion the author states that, contrary to his theoretical principles, Reichenbach actually resorts to a non-statistical interpretation of probability in some of his contexts; his reasoning is insufficient for the foundation of the direct rule; pragmatic justification of induction is irrelevant to any interpretation of probability, except statistical.